STRATEGIES FOR INCREASING PSYCHOLOGICAL LITERACY OF THE LOCAL POPULATION - Umrzaqova Gulchehra Abdurasuljon qizi (Modern American Journals, 2025)
This article analyzes the relevance of increasing the psychological literacy of the local population, the main strategies and effective ways to implement them.
Keywords: Psychological literacy, educational activities, strategy, neighborhood, online resources.